2015
DOI: 10.1038/ncomms7575
|View full text |Cite
|
Sign up to set email alerts
|

Impedance sensing device enables early detection of pressure ulcers in vivo

Abstract: When pressure is applied to a localized area of the body for an extended time, the resulting loss of blood flow and subsequent reperfusion to the tissue causes cell death and a pressure ulcer develops. Preventing pressure ulcers is challenging because the combination of pressure and time that results in tissue damage varies widely between patients, and the underlying damage is often severe by the time a surface wound becomes visible. Currently, no method exists to detect early tissue damage and enable interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
151
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 205 publications
(153 citation statements)
references
References 34 publications
2
151
0
Order By: Relevance
“…[ 101 ] Inkjet printing is well adept for depositing sparse, thin designs but becomes diffi cult for larger-sized features. [ 7,109,110 ] Gravure and fl exographic printing require higher viscosity inks for reliable printing. [ 101 ] While formulating high viscosity inks necessitates the use of highly soluble solutes, features as small as 5 µm can be reliably printed at speeds approaching one meter per second.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 101 ] Inkjet printing is well adept for depositing sparse, thin designs but becomes diffi cult for larger-sized features. [ 7,109,110 ] Gravure and fl exographic printing require higher viscosity inks for reliable printing. [ 101 ] While formulating high viscosity inks necessitates the use of highly soluble solutes, features as small as 5 µm can be reliably printed at speeds approaching one meter per second.…”
Section: Reviewmentioning
confidence: 99%
“…[ 2,3 ] Alternative materials, such as plastic and elastomeric substrates, used in these fl exible devices are conformal by nature, lightweight, and therefore offer better interface with the human skin and soft tissue. Many sensors also use electronic and optoelectronic materials that are fl exible by nature [4][5][6][7] while other approaches look into transferring small and thin conventional devices onto fl exible substrates. [ 8,9 ] Meanwhile, silicon-based electronics provide unparalleled performance in data processing and performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase plot (Figure 3b) revealed a lower phase angle for Labskin compared to human skin. It has been suggested that a higher phase angle can be indicative of healthier cell membranes in the context of wound healing in vivo, however, this requires further investigation in HSEs to understand the implications of phase angle in studies in vitro [35,36].…”
Section: Biophysical Properties and Temporary Tattoo Sensorsmentioning
confidence: 99%
“…The electrode material must have a low impedance and also be compatible with lithography and patterning techniques. Gold [40], [41], [77], [107], [109], [112], [121], [122], [126], [129]- [132], [136], [138], [139], [141], [147], [148], platinum [125], [134], [142], indium tin oxide (ITO) [118], [124], [140], [146], iridium [120], [128], [147], polysilicon [149], and carbon [150] have all been used as electrode materials. The electrode material can be sputtered, evaporated, deposited by PECVD, or even screen printed.…”
Section: Electrode Materialsmentioning
confidence: 99%